Oskar Is Targeted for Degradation by the Sequential Action of Par-1, GSK-3, and the SCF(-Slimb) Ubiquitin Ligase. - Morais-de-Sá, E.; Vega-Rioja, A.; Trovisco, V.; St Johnston, D. (Developmental Cell, 2013)
Translation of oskar messenger RNA (mRNA) is activated at the posterior of the Drosophila oocyte, producing Long Oskar, which anchors the RNA, and Short Oskar, which nucleates the pole plasm, containing the posterior and germline determinants. Here, we show that Oskar is phosphorylated by Par-1 and GSK-3/Shaggy to create a phosphodegron that recruits the SCF(-Slimb) ubiquitin ligase, which targets Short Oskar for degradation. Phosphorylation site mutations cause Oskar overaccumulation, leading to an increase in pole cell number and embryonic patterning defects. Furthermore, the nonphosphorylatable mutant produces bicaudal embryos when oskar mRNA is mislocalized. Thus, the Par-1/GSK-3/Slimb pathway plays important roles in limiting the amount of pole plasm posteriorly and in degrading any mislocalized Oskar that results from leaky translational repression. These results reveal that Par-1 controls the timing of pole plasm assembly by promoting the localization of oskar mRNA but inhibiting the accumulation of Short Oskar protein.